Electrolyte solution, secondary battery, and electric device

By using lithium nitrate and electrolyte with specific additives in lithium batteries, a SEI film with high toughness and strength is formed, which solves the problem of insufficient cycle stability and fast charging performance of lithium batteries, and improves battery performance.

CN119725729AActive Publication Date: 2025-03-28CHONGQING FUDI BATTERY RES INST CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311262371.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

The SEI film performance of existing lithium batteries is insufficient, resulting in poor battery cycle stability and poor fast charging performance.

Method used

An electrolyte containing lithium nitrate and a specific additive is used, which can undergo an addition polymerization reaction under electrochemical catalysis to form a flexible polymer, which enhances the toughness of the SEI film and increases the strength and ionic conductivity of the SEI film through Li3N.

Benefits of technology

The cycle stability and fast charging performance of the battery are improved, the toughness and ionic conductivity of the SEI film are enhanced, and the negative electrode interface of the battery is optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004473359290000011
    Figure BDA0004473359290000011
  • Figure BDA0004473359290000021
    Figure BDA0004473359290000021
  • Figure BDA0004473359290000031
    Figure BDA0004473359290000031
Patent Text Reader

Abstract

The invention provides an electrolyte, a secondary battery and electric equipment. The lithium nitrate and the additive in the electrolyte can jointly form a film on the surface of an electrode plate, and the cycle performance, the high-temperature storage performance and the fast charging performance of the battery can be considered.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments of the present application relate to the field of battery technology, and specifically to electrolytes, secondary batteries, and electrical equipment. Background Art

[0002] With the popularization and widespread application of digital smart products and new energy vehicles, the market has put forward higher requirements for the battery life and charging speed of lithium batteries installed in the above-mentioned electrical equipment. A large number of studies have found that the solid electrolyte interface (SEI) film on the surface of the negative electrode plays a vital role in the performance of the battery, and the composition of the electrolyte greatly affects the performance of the SEI film.

[0003] In the related technology, the strength, toughness and other properties of the battery SEI membrane are poor. During multiple cycles of the battery, the SEI membrane is prone to rupture, which seriously affects the cycle stability of the battery. In addition, if the ionic conductivity of the SEI membrane is poor, it is not conducive to achieving the fast charging performance of the battery. Summary of the invention

[0004] In view of this, the present application provides an electrolyte, in which the lithium nitrate and additives can form a film together on the surface of the electrode plate, which can take into account the battery's cycle performance, high-temperature storage performance and fast charging performance.

[0005] In a first aspect, the present application provides an electrolyte, comprising lithium nitrate and an additive as shown in formula (I);

[0006]

[0007] Wherein, at least one of R1, R2, R3 and R4 contains an unsaturated bond that can undergo addition polymerization reaction, and at least one of R1, R2, R3 and R4 contains an -OC bond, and the -OC bond is connected to a silicon atom or a carbon atom.

[0008] The lithium nitrate and additives in the above electrolyte can participate in the formation of the SEI film on the surface of the negative electrode. The additives can undergo a polymerization reaction under electrochemical catalysis to form a polymer. Because the additives contain both Si atoms and -OC bonds, and the -OC bonds are connected to silicon atoms or carbon atoms, the polymers formed after the polymerization are flexible, which can improve the toughness of the SEI film to better adapt to the volume expansion / contraction of the negative electrode material during the charge and discharge process, thereby making the SEI film continuously stable during the battery charge and discharge cycle; while improving the storage stability of the battery. In addition, Li3N generated by the lithium nitrate reaction can improve the strength and ionic conductivity of the SEI film, and the above electrolyte can generate a stable, tough and high ionic conductivity SEI film on the surface of the negative electrode, optimize the negative electrode interface, and at the same time improve the fast charging performance and cycle stability of the battery.

[0009] In addition, the above additives and lithium nitrate can also participate in the film formation on the positive electrode surface, generating a cathode electrolyte interface (CEI) film on the positive electrode surface that has strength, toughness and high ionic conductivity. The CEI film and the above SEI film synergistically improve the performance of the battery.

[0010] Optionally, the unsaturated bond includes a carbon-carbon double bond and / or a carbon-carbon triple bond.

[0011] Optionally, the R1, R2, R3 and R4 are each independently selected from a substituted or unsubstituted hydrocarbon group containing the unsaturated bond and / or the -OC bond.

[0012] Optionally, one or two of R1, R2, R3 and R4 contain the unsaturated bond.

[0013] Optionally, the -OC bond is connected to a Si atom.

[0014] Optionally, the number of carbon atoms in R1, R2, R3 and R4 is each independently a positive integer of 1 to 12.

[0015] Optionally, R1, R2, R3 and R4 are each independently a group other than an H atom and a hydroxyl group.

[0016] Optionally, the substituted or unsubstituted hydrocarbon group containing the unsaturated bond includes vinyl and / or ethynyl; the substituted or unsubstituted hydrocarbon group containing the -OC bond includes at least one of methoxy, ethoxy, 2-methoxyethoxy and phenoxy.

[0017] Furthermore, the additive comprises at least one of formula (A) to formula (E),

[0018]

[0019] Optionally, based on the total mass of the electrolyte, the content of the additive is in the range of 0.1% to 5%.

[0020] Optionally, the mass content of the lithium nitrate in the electrolyte is in the range of 0.1% to 5%.

[0021] Optionally, the electrolyte further comprises lithium bis(fluorosulfonyl)imide. Further, the mass content of lithium bis(fluorosulfonyl)imide in the electrolyte is in the range of 1% to 15.6%.

[0022] Optionally, the electrolyte further comprises a fluoroether solvent as shown in formula (II),

[0023]

[0024] Wherein, R5 and R6 are fluoroalkyl groups, wherein the number of carbon atoms of the fluoroalkyl group is a positive integer of 1 to 12.

[0025] Optionally, the electrolyte further comprises a carbonate solvent. Further, the mass ratio of the fluoroether solvent to the carbonate solvent is 1:(1-19).

[0026] Optionally, the electrolyte further includes an electrolyte salt; the electrolyte salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium sulfate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonate), lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium dioxalatoborate and lithium perchlorate.

[0027] The second aspect of the present application provides a secondary battery, comprising a negative electrode; at least the surface of the negative electrode has a solid electrolyte interface film,

[0028] The solid electrolyte interface film includes a silicon-containing flexible polymer and Li3N.

[0029] Li3N in the above-mentioned solid electrolyte interface (SEI) film can improve the strength and ionic conductivity of the SEI film, while the silicon-containing flexible polymer can improve the toughness of the SEI film. Therefore, the above-mentioned solid electrolyte membrane has good toughness, high strength and ionic conductivity, which can optimize the negative electrode interface of the battery and improve the fast charging performance and cycle stability of the battery.

[0030] Optionally, the silicon-containing flexible polymer comprises a polymerization product of at least one additive as represented by formula (I);

[0031]

[0032] Wherein, at least one of R1, R2, R3 and R4 contains an unsaturated bond that can undergo addition polymerization reaction, and at least one of R1, R2, R3 and R4 contains an -OC bond, and the -OC bond is connected to a silicon atom or a carbon atom.

[0033] Optionally, the secondary battery includes the electrolyte provided in the first aspect of the embodiment of the present application.

[0034] Optionally, the negative electrode includes a current collector and a negative electrode active material layer disposed on at least one side of the current collector, and the negative electrode active material layer includes a silicon-based negative electrode material.

[0035] The third aspect of the present application provides an electric device, including the battery provided in the second aspect of the present application. Since the battery provided in the second aspect of the present application is used to power the device, the electric device can achieve stable fast charging and has a good market prospect.

[0036] Optionally, the electrical equipment includes consumer electronic products and vehicles. DETAILED DESCRIPTION

[0037] After extensive research, it is now generally believed that the SEI membrane of lithium-ion batteries has a multilayer structure. The SEI membrane generally includes a double-layer structure, the outer layer (close to the electrolyte side) generally includes porous organic components, and the inner layer (close to the active material side) includes dense inorganic components. In lithium-ion batteries, the performance of the SEI membrane also plays a vital role in the stability and fast charging performance of the battery. The ideal SEI membrane should have high ionic conductivity, good electronic insulation, high strength and toughness, and high uniformity, but the general SEI membrane is either brittle, poor stability in multiple charge and discharge cycles of the battery, easy to break, causing safety accidents; or high impedance, unable to meet the fast charging performance requirements of the battery. In addition, insufficient ionic conductivity will also affect the fast charging performance of the battery. For example, when the battery is fast charged, the speed at which lithium ions pass through the SEI membrane is slower than the deposition speed of lithium at the negative electrode, resulting in a large polarization at the negative electrode interface, which will lead to the continuous formation of lithium dendrites at the negative electrode, causing the lithium-ion battery to short-circuit and even cause explosions.

[0038] To solve the above problems, the present application provides an electrolyte solution, comprising lithium nitrate and an additive as shown in formula (I);

[0039]

[0040] Wherein, at least one of R1, R2, R3 and R4 contains an unsaturated bond that can undergo addition polymerization, and at least one of R1, R2, R3 and R4 contains an -OC bond, and the -OC bond is connected to a silicon atom or a carbon atom. It can be understood that here specifically refers to the oxygen atom in the -OC bond being connected to a silicon atom or a carbon atom.

[0041] In the present specification, "unsaturated bond" specifically refers to "unsaturated bond that can undergo addition polymerization reaction", unless otherwise specified.

[0042] In the embodiments of the present application, one additive molecule may contain a Si-OC bond but no COC bond; may contain a COC bond but no Si-OC bond; or may contain both a Si-OC bond and a COC bond.

[0043] In the embodiments of the present application, the above-mentioned unsaturated bonds and -OC bonds may exist in one side chain at the same time (for example, the above-mentioned unsaturated bonds and -OC bonds exist in R1 at the same time); or they may exist in two different side chains respectively (for example, the above-mentioned unsaturated bonds exist in R1 and the -OC bonds exist in R2); or some unsaturated bonds and some -OC bonds may exist in one side chain at the same time, and other unsaturated bonds and / or other -OC bonds may exist in different side chains respectively (for example, R1 contains the above-mentioned unsaturated bonds and -OC bonds at the same time, R2 is a hydrocarbon group containing the above-mentioned unsaturated bonds, and R3 and R4 are hydrocarbon groups containing -OC bonds).

[0044] During the battery charging process, the components of the electrolyte (including additives, lithium nitrate and solvent) can react under the catalysis of electrochemistry and temperature, and can form a SEI film on the surface of the negative electrode; wherein, since the additive has an unsaturated bond that can undergo an addition polymerization reaction, it can undergo an addition polymerization reaction to form a polymer, and the polymer is mainly located on the side of the SEI film close to the electrolyte, and the additive contains both Si atoms and the above-mentioned -OC bond, and the -OC bond is connected to the Si atom or C atom, so the polymer formed by the additive has good flexibility and can improve the toughness of the SEI film; therefore, during the battery charging and discharging process, the SEI film can expand / contract accordingly with the expansion / contraction of the negative electrode material, which can slow down the rupture of the SEI film, has good stability, and can improve the cycle stability of the battery. At the same time, the lithium nitrate in the electrolyte, as an additive, will also react to generate inorganic substances with high ionic conductivity such as Li3N, and is mainly formed on the side of the SEI film close to the negative electrode to simultaneously improve the strength and ionic conductivity of the SEI film. Among them, improving the strength of the SEI film can reduce side reactions during the battery cycle, making the SEI film "strong inside and soft outside", which helps to improve the high-temperature storage stability of the battery and extend the battery's cycle life; and Li3N can also improve the ionic conductivity of the SEI film, improve the battery's rate performance, and thus improve the battery's fast charging performance, that is, the battery can be fast-charged in a long-lasting, stable and safe manner. In summary, the above-mentioned electrolyte can improve the fast charging performance, storage and cycle stability of batteries (especially high energy density system batteries).

[0045] In addition, the above-mentioned additives and lithium nitrate can also participate in the formation of the cathode electrolyte interface (CEI) film. The CEI film finally formed can cooperate with the SEI film to improve the cycle performance and fast charging performance of the battery. Its function and principle are similar to those of the SEI film and will not be repeated here.

[0046] In some embodiments of the present application, the unsaturated bonds that can undergo addition polymerization are selected from carbon-carbon double bonds and / or carbon-carbon triple bonds. Carbon-carbon double bonds and carbon-carbon triple bonds can undergo addition polymerization without introducing active functional groups into the electrolyte, which can reduce the risk of side reactions between substances in the electrolyte and between the electrolyte and other substances in the battery cell, making the performance of the electrolyte more stable, and further ensuring the normal performance of the battery.

[0047] In the embodiment of the present application, R1, R2, R3 and R4 can be independently selected from a substituted or unsubstituted hydrocarbon group containing an -OC bond and / or an unsaturated bond, a substituted or unsubstituted ester group containing an -OC bond and / or an unsaturated bond, a substituted or unsubstituted aldehyde group containing an -OC bond and / or an unsaturated bond, a substituted or unsubstituted carboxyl group containing an -OC bond and / or an unsaturated bond, a substituted or unsubstituted amino group containing an -OC bond and / or an unsaturated bond, a substituted or unsubstituted amide group containing an -OC bond and / or an unsaturated bond, etc. Further, the above groups can also contain substituted groups, wherein the substituted groups include but are not limited to halogen atoms, for example, F atoms, Cl atoms, etc.

[0048] In some embodiments of the present application, R1, R2, R3 and R4 are each independently selected from substituted or unsubstituted hydrocarbon groups containing -OC bonds and / or unsaturated bonds. Further, the above hydrocarbon groups are substituted hydrocarbon groups.

[0049] In some embodiments of the present application, the R1, R2, R3 and R4 are each independently a substituted or unsubstituted hydrocarbon group containing an unsaturated bond that can undergo an addition polymerization reaction or a substituted or unsubstituted hydrocarbon group containing an -OC bond. In this way, in the additive molecule, the unsaturated group and the -OC bond belong to different side chains, so the flexible segment is used as a side chain in the final polymer, which is more conducive to improving the flexibility of the SEI. Further, in some specific embodiments, two of R1, R2, R3 and R4 are substituted or unsubstituted hydrocarbon groups containing the above-mentioned unsaturated bonds, and the other two are substituted or unsubstituted hydrocarbon groups containing -OC bonds. In this way, the crosslinking degree and flexibility of the additive polymer can be better taken into account, that is, the strength and toughness of the polymer in the SEI film are high, and the continuous stability of the SEI during the battery cycle is further improved. In some embodiments of the present application, the above-mentioned hydrocarbon group containing an -OC bond includes but is not limited to substituted or unsubstituted alkyl, substituted or unsubstituted phenyl (e.g., benzyl), etc. Furthermore, in some specific embodiments, the hydrocarbon group containing the -OC bond is an alkoxy group, which is more conducive to ensuring that the flexibility of the polymer is higher.

[0050] In some embodiments of the present application, one or two of the R1, R2, R3 and R4 contain unsaturated bonds that can undergo addition polymerization. In this way, the degree of crosslinking of the final polymer can be controlled within an appropriate range, further ensuring that the polymer has high flexibility, which is beneficial for the SEI film to change with the volume change of the negative electrode active material, and thus more beneficial to the cycle performance of the battery. Here, for the convenience of description, R1, R2, R3 and R4 are collectively referred to as "side groups"; when a single side group contains only one of the above unsaturated bonds, the number of unsaturated bonds that can undergo addition polymerization in an additive with a molecular structure is less than or equal to 2; when a single side group contains multiple unsaturated bonds (for example, the side group is -C=CCCC=C), only one or two side groups contain the above unsaturated bonds, and there is no limit on the total number of unsaturated bonds in the first additive with a molecular structure. Further, in some specific examples, when a single side group contains multiple unsaturated bonds, the side group is a non-conjugated system.

[0051] In some embodiments of the present application, the -OC bond is connected to the Si atom; that is, the additive has a molecule structure containing a Si-OC bond. The bond length of the Si-O bond is greater than that of the Si-C bond, and the Si-O bond is more flexible, which is more conducive to improving the toughness of the SEI film, and therefore, is more conducive to the performance of the battery.

[0052] In some embodiments of the present application, an additive with a molecular structure may contain multiple -OC bonds. For the convenience of description, R1, R2, R3 and R4 are collectively referred to as "side groups". Specifically, multiple side groups may contain -OC bonds, so that an additive with a molecular structure contains multiple -OC bonds; or a single side group may contain multiple -OC bonds; or a single side group may contain multiple -OC bonds at the same time, and multiple side groups may contain the above-mentioned -OC bonds at the same time. Increasing the number of -OC bonds is more conducive to improving the toughness of the final SEI film. The above-mentioned -OC bonds have greater reactivity. Controlling the number of -OC bonds in an additive with a molecular structure within an appropriate range can reduce the risk of side reactions with other substances in the battery cell, which is beneficial to the performance of the battery.

[0053] In some embodiments of the present application, the number of carbon atoms in R1, R2, R3 and R4 is independently a positive integer of 1 to 12. Controlling the number of carbon atoms in R1, R2, R3 and R4 within the above range can improve the solubility of the additive in the electrolyte, thereby ensuring the good performance of the SEI film and the CEI film, and also conducive to the performance of the battery. Exemplarily, the number of carbon atoms in R1, R2, R3 and R4 can be independently 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12.

[0054] In some embodiments of the present application, R1, R2, R3 and R4 are not hydrogen atoms and hydroxyl groups. That is, R1, R2, R3 and R4 are not hydrogen atoms and are not hydroxyl groups. In this way, the risk of additives and polymers formed by additives affecting battery performance can be fully reduced.

[0055] In some embodiments of the present application, the substituted or unsubstituted hydrocarbon group containing an unsaturated bond that can undergo addition polymerization reaction includes but is not limited to vinyl and / or ethynyl; the substituted or unsubstituted hydrocarbon group containing -OC bond includes but is not limited to at least one of methoxy, ethoxy, 2-methoxyethoxy and phenoxy. In some specific embodiments, the additive includes at least one of formula (A) to formula (E),

[0056]

[0057]

[0058] Among them, the CAS number of the substance represented by formula (A) is 17985-63-6; the CAS number of the substance represented by formula (B) is 873703-35-6; the CAS number of the substance represented by formula (C) is 129762-81-8; the CAS number of the substance represented by formula (D) is 144967-39-5; and the CAS number of the substance represented by formula (E) is 67892-60-8.

[0059] In some specific embodiments, the additive includes a structure as shown in formula (E), that is, divinyldiethoxysilane. The substance of the molecular structure contains two carbon-carbon double bonds that can undergo addition polymerization and two highly flexible ethoxy groups. The SEI film finally formed has a suitable cross-linking degree and toughness, and can reduce the risk of introducing side reactions to cause deterioration of battery performance, thereby being more conducive to taking into account the storage stability and cycle life of the battery.

[0060] In some embodiments of the present application, the mass percentage of the above-mentioned additive is in the range of 0.1% to 5% based on the total mass of the electrolyte. For example, the mass percentage of the additive in the electrolyte can be 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, 4.5%, 4.8%, etc. By controlling its content within the above range, the total thickness of the SEI film can be controlled within a suitable range, so that the interfacial impedance of the battery is small, which is conducive to the rapid charging and discharging of the battery; and the SEI film can have good toughness, inhibit the rupture of the SEI film, and help improve the cycle performance of the battery.

[0061] In some embodiments of the present application, the mass percentage of lithium nitrate is in the range of 0.1% to 5% based on the total mass of the electrolyte. For example, the mass percentage of lithium nitrate in the electrolyte can be 0.1%, 0.2%, 0.5%, 0.8%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, 4.5%, 4.8%, etc. Controlling the mass content of lithium nitrate within the above range can not only fully improve the strength and ionic conductivity of the SEI film, but also avoid the waste caused by the insolubility of excessive lithium nitrate, and control the production cost.

[0062] In some embodiments of the present application, the electrolyte also includes lithium bis(fluorosulfonyl)imide (LiFSI). The addition of lithium bis(fluorosulfonyl)imide not only improves the stability of the electrolyte salt, but also helps to reduce the impedance of the SEI film and is beneficial to the ionic conductivity of the SEI film. Preferably, in some specific embodiments, the mass content of lithium bis(fluorosulfonyl)imide in the electrolyte is in the range of 1% to 15.6%. It can be understood that LiFSI is also a common electrolyte salt. When its mass content in the electrolyte is high, a part of it participates in the formation of the SEI film as an additive during the battery formation process, and the remaining LiFSI participates in the subsequent charge and discharge cycles as an electrolyte salt. Exemplarily, the mass percentage of LiFSI in the electrolyte can be 1.0%, 1.2%, 1.5%, 2.0%, 2.2%, 2.5%, 3.0%, 3.2%, 3.5%, 3.8%, 4.0%, 4.2%, 4.5%, 5.0%, 6.0%, 7.0%, 8.0%, 9.0%, 10.0%, 11.0%, 12.0%, 13.0%, 14.0%, 15.0%, 15.5%, etc. Preferably, in some specific embodiments, the mass percentage of LiFSI in the electrolyte is in the range of 1% to 5%. In this way, the performance of the SEI film can be improved, and the risk of corrosion of the positive electrode collector can be fully reduced, thereby further ensuring the performance of the battery.

[0063] In some embodiments of the present application, the electrolyte further comprises at least one fluoroether solvent as shown in formula (II), Wherein, the R5 and R6 are fluoroalkyl groups. Specifically, the R5 and R6 can be perfluoroalkyl groups or partially fluoroalkyl groups. Wherein, the number of carbon atoms of the fluoroalkyl group is a positive integer of 1-12. Exemplarily, the number of carbon atoms of the fluoroalkyl group can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12. The fluoroether solvent can reduce the viscosity of the electrolyte, increase the solubility of the electrolyte (for example, the solubility of the electrolyte), increase the wettability of the electrolyte to the negative electrode sheet, the positive electrode sheet and the diaphragm, and improve the oxidation resistance of the electrolyte to improve the comprehensive electrochemical performance of the battery. In some specific embodiments, the R5 and R6 can be independently selected from one or two of monofluoromethyl, difluoromethyl, trifluoromethyl, monofluoroethyl, difluoroethyl and trifluoroethyl.

[0064] In some embodiments of the present application, the electrolyte further comprises a carbonate solvent. In some embodiments of the present application, the carbonate solvent includes but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), etc. In some specific embodiments, the above-mentioned carbonate solvents include cyclic carbonates and linear carbonates at the same time, the cyclic carbonates include ethylene carbonate, and the linear carbonates include at least one of diethyl carbonate, dimethyl carbonate and methyl ethyl carbonate. The dielectric constant of cyclic carbonates is high and the viscosity of linear carbonates is low. The combination of the two is beneficial to improving the ionic conductivity of the electrolyte. In some specific embodiments, the carbonate solvent includes EC:DEC:EMC in a mass ratio of (2-4):(2-3):(4-5). Illustratively, the mass ratio of EC:DEC:EMC can be 2:(2-3):(4-5), 2.5:(2-3):(4-5), 3:(2-3):(4-5), 3.5:(2-3):(4-5), 4.0:(2-3):(4-5), (2-4):2:(4-5), (2-4):2.5:(4-5), (2-4):(2-3):4.5, etc.

[0065] In some specific embodiments of the present application, the mass ratio of the fluoroether solvent to the carbonate solvent is 1:(1-19). For example, the mass ratio of the fluoroether solvent to the carbonate solvent can be 1:1, 1:2, 1:5, 1:8, 1:10, 1:12, 1:15, 1:18, 1:19, etc. By controlling the mass ratio of the two within the above range, the electrolyte has a more suitable viscosity and can better infiltrate the electrode plate; at the same time, an appropriate amount of carbonate solvent is conducive to improving the voltage window of the electrolyte to meet the needs of high energy density of the battery.

[0066] In some embodiments of the present application, the electrolyte also includes an electrolyte salt; the electrolyte salt includes but is not limited to at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium sulfate (Li2SO4), lithium difluorooxalatoborate (abbreviated as LiDFOB), lithium dioxalatoborate (abbreviated as LiBOB), lithium bis(trifluoromethanesulfonyl)imide (abbreviated as LiTFSI), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (abbreviated as LiTFA or LiOTF) and lithium perchlorate (LiClO4).

[0067] In some embodiments of the present application, the molar concentration of the electrolyte salt in the electrolyte is 0.8mol / L-1.2mol / L. It should be noted that when the electrolyte also contains LiFSI, it needs to be discussed separately: when the mass content percentage of LiFSI in the electrolyte is less than or equal to 5.0%, LiFSI only exists as an additive, and LiFSI is not included in the calculation of the electrolyte salt concentration; and when the mass content percentage of LiFSI in the electrolyte is greater than 5.0%, LiFSI less than or equal to 5.0% is used as an additive, and the LiFSI exceeding 5.0% is counted as an electrolyte salt and calculated into the concentration of the electrolyte salt. In addition, lithium nitrate is not included in the calculation of the electrolyte salt concentration.

[0068] The present application also provides a battery, comprising a negative electrode; at least the surface of the negative electrode has a solid electrolyte interface film,

[0069] The solid electrolyte interface film includes a silicon-containing flexible polymer and Li3N.

[0070] Li3N in the above-mentioned solid electrolyte interface (SEI) film can improve the strength and ionic conductivity of the SEI film, while the silicon-containing flexible polymer can improve the toughness of the SEI film. Therefore, the above-mentioned solid electrolyte membrane has good toughness, high strength and ionic conductivity, which can optimize the negative electrode interface of the battery and improve the fast charging performance and cycle stability of the battery.

[0071] Of course, in some embodiments, the battery further includes a positive electrode, the surface of the positive electrode has a positive electrode electrolyte interface film (CEI), and the CEI includes the above-mentioned silicon-containing flexible polymer and Li3N. The modification principle of the CEI film by the silicon-containing flexible polymer and Li3N is similar to that of the SEI film, which will not be repeated here. The above-mentioned CEI film can synergistically improve the cycle, storage stability and fast charging performance of the battery.

[0072] In some embodiments of the present application, the silicon-containing flexible polymer includes a polymerization product of at least one additive as shown in formula (I);

[0073]

[0074] Among them, at least one of the R1, R2, R3, and R4 contains an unsaturated bond capable of addition polymerization reaction, and at least one of the R1, R2, R3, and R4 contains an -O-C bond, and the -O-C bond is connected to an Si atom or a C atom. Thus, the silicon-containing flexible polymer has both a certain strength and good flexibility.

[0075] In some embodiments of the present application, the secondary battery includes the electrolyte provided in the embodiments of the present application.

[0076] In some embodiments of the present application, the above-mentioned negative electrode can be any negative electrode well-known in the art. In some specific embodiments, the negative electrode includes a negative electrode current collector and a negative electrode active material layer provided on at least one side of the negative electrode current collector. Among them, the negative electrode active material includes, but is not limited to, one or more of carbon-based negative electrodes, silicon-based negative electrodes, and tin-based negative electrodes. Among them, the carbon-based negative electrode can include graphite, hard carbon, soft carbon, graphene, etc.; the silicon-based negative electrode can include silicon, silicon carbide, silicon oxide, silicon metal compounds, etc.; the tin-based negative electrode can include tin, tin carbide, tin oxide, tin metal compounds. In some specific embodiments, the above-mentioned negative electrode active material is selected from at least one of silicon monoxide, silicon carbide, and silicon-carbon composite. The above-mentioned negative electrode active material is not only more suitable for liquid lithium-ion batteries, and the main material of the above-mentioned silicon-based negative electrode is silicon. Under certain conditions, the improvement effect of the additive on the silicon-based negative electrode is better.

[0077] In the present application, the above-mentioned positive electrode is any positive electrode sheet well-known in the art. In some embodiments, the above-mentioned positive electrode includes a positive electrode current collector and a positive electrode active material layer provided on at least one side thereof. Among them, the positive electrode active material is any positive electrode active material well-known in the art. Exemplarily, it includes, but is not limited to, lithium cobaltate (LiCoO2), lithium nickelate (LiNiO2), lithium iron phosphate (LiFePO4), lithium cobalt phosphate (LiCoPO4), lithium manganese phosphate (LiMnPO4), lithium nickel phosphate (LiNiPO4), lithium manganate (LiMnO2), binary material LiNi x A (1-k) O2 (wherein A is selected from one of Co and Mn, 0 < k < 1), ternary material LiNimEnM (1-m-n) O2 (wherein E and M are independently selected from at least one of Co, Al, and Mn, and E and M are different, 0 < m < 1, 0 < n < 1).

[0078] In some embodiments of the present application, the negative electrode active material layer and the positive electrode active material layer each independently include a conductive agent and a binder. In the present application, the above-mentioned binder and conductive agent are selected from any binder and conductive agent known in the art. In some embodiments, the conductive agent in the positive electrode sheet and the negative electrode sheet can be independently selected from at least one of acetylene black, SuperP, Super S, graphene, carbon fiber, carbon nanotubes and Ketjen black.

[0079] In some embodiments of the present application, a separator is provided between the positive electrode and the negative electrode. In the present application, the separator is any separator known in the art.

[0080] The embodiment of the present application also provides an electric device, which includes the secondary battery provided in the embodiment of the present application. Since the battery provided in the second aspect of the present application is used to power the device, the electric device can achieve stable fast charging and has a good market prospect.

[0081] In some implementation methods of the present application, the above-mentioned electrical equipment includes but is not limited to 3C electronic equipment, new energy vehicles, electric assisted bicycles, etc.

[0082] The technical solution of the present application is further illustrated by multiple embodiments below.

[0083] Example 1

[0084] In a glove box filled with argon gas and with a water content and oxygen content of less than 1ppm, an electrolyte is prepared. The electrolyte includes a carbonate solvent, an additive (specifically divinyldiethoxysilane) with a mass percentage of 0.5%, and lithium nitrate and an electrolyte salt (specifically LiPF6) with a mass percentage of 1.0%. The molar concentration of LiPF6 in the electrolyte is 1 mol / L. The carbonate solvent includes ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a mass ratio of 30:30:40.

[0085] Example 2

[0086] The only difference from Example 1 is that the electrolyte further includes LiFSI with a mass percentage of 3.0%.

[0087] Example 3

[0088] The difference from Example 1 is that the electrolyte also includes 3.0% by mass of LiFSI, and the solvent of the electrolyte also includes a fluoroether solvent (specifically dimethyl ether). Specifically, the electrolyte formula is: ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate: dimethyl ether with a mass ratio of 27:27:36:10 solvent, and 0.5% by mass of additives (specifically divinyldiethoxysilane, structure shown in formula (E)), 1.0% by mass of lithium nitrate, 3.0% by mass of LiFSI, and an electrolyte salt with a molar concentration of 1 mol / L (specifically LiPF6).

[0089] Example 4

[0090] The difference from Example 3 is that dimethyl ether is replaced by an equal mass of bis(trifluoromethyl) ether, and the electrolyte does not contain LiFSI.

[0091] Example 5

[0092] The difference from Example 3 is that the mass percentage of LiFSI in the electrolyte is 6%, and the content of LiPF6 is slightly adjusted so that the molar concentration of the electrolyte salt in the electrolyte is 1 mol / L (the part of LiFSI with a mass percentage exceeding 5% is calculated as electrolyte salt, that is, based on the total mass of the electrolyte, 1 wt.% of LiFSI is calculated as electrolyte salt).

[0093] Example 6

[0094] The only difference from Example 3 is that dimethyl ether is replaced by an equal mass of bis(trifluoromethyl) ether.

[0095] Example 7

[0096] The difference from Example 3 is that dimethyl ether is replaced by an equal amount of bis(trifluoromethyl) ether, and the mass percentage of lithium nitrate is increased to 2.0%.

[0097] Example 8

[0098] The difference from Example 7 is that the mass percentage of lithium nitrate in the electrolyte is 0.1%.

[0099] Example 9

[0100] The difference from Example 7 is that the mass percentage of lithium nitrate in the electrolyte is 5.0%.

[0101] Example 10

[0102] The difference from Example 7 is that the mass percentage of the additive in the electrolyte is 0.1%.

[0103] Embodiment 11

[0104] The difference from Example 7 is that the mass percentage of the additive in the electrolyte is 3.0%.

[0105] Example 12

[0106] The difference from Example 7 is that the mass percentage of the additive in the electrolyte is 5.0%.

[0107] Embodiment 13

[0108] The difference from Example 7 is that the mass percentage of the additive in the electrolyte is 7.0%.

[0109] Embodiment 14

[0110] The difference from Example 7 is that the additive is replaced by divinyldiethoxysilane with a structure as shown in formula (A),

[0111]

[0112] Embodiment 15

[0113] The difference from Example 7 is that the additive is replaced with the structure shown in (B),

[0114] Example 16

[0115] The difference from Example 7 is that the additive is replaced with a structure as shown in (C),

[0116] Embodiment 17

[0117] The difference from Example 7 is that the additive is replaced with a structure as shown in (D),

[0118] Embodiment 18

[0119] The difference from Example 7 is that the additive is replaced by

[0120] Embodiment 19

[0121] The difference from Example 7 is that the additive is replaced by

[0122] In order to highlight the beneficial effects of the embodiments of the present application, the following comparative examples are provided.

[0123] Comparative Example 1

[0124] In a glove box filled with argon gas and with a water content and oxygen content of less than 1 ppm, an electrolyte was prepared, wherein the electrolyte included ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a mass ratio of 30:30:40, 3.0% of LiFSI by mass, and the electrolyte salt was LiPF6 at a concentration of 1 mol / L.

[0125] Comparative Example 2

[0126] In a glove box filled with argon gas and with a water content and oxygen content of less than 1ppm, an electrolyte was prepared, wherein the electrolyte included ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a mass ratio of 30:30:40, 3.0% LiFSI by mass, 0.1% lithium nitrate by mass, and the electrolyte salt was LiPF6 at a concentration of 1 mol / L.

[0127] Comparative Example 3

[0128] In a glove box filled with argon with a water content and an oxygen content of less than 1ppm, an electrolyte was prepared. The electrolyte included ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate: di(trifluoromethyl) ether in a mass ratio of 27:27:36:10, 3.0% LiFSI by mass, 1.0% additive (specifically divinyldiethoxysilane) by mass, and the electrolyte salt was LiPF6 at a concentration of 1 mol / L.

[0129] Performance Testing

[0130] (1) Prepare test cells containing the electrolytes of the embodiment and the comparative example respectively: prepare positive electrode sheets, negative electrode sheets and separators (specifically polypropylene separators), wherein the positive electrode sheets include positive electrode current collectors (specifically aluminum foil) and positive electrode active material layers, and the positive electrode active material layers include positive electrode active materials (specifically LiNi 0.8 Co 0.1 Mn 0.1O2, also known as NCM811), a conductive agent (specifically Super P), a binder (specifically polyvinylidene fluoride, PVDF); the negative electrode plate includes a negative electrode current collector (specifically copper foil) and a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material (specifically graphite), a conductive agent (specifically Super P), and a binder (specifically 1 weight part of sodium carboxymethyl cellulose (CMC) + 1.6 weight parts of styrene-butadiene rubber (SBR)) in a mass ratio of 96.00:1.40:2.60; a diaphragm is placed between the positive electrode plate and the negative electrode plate to separate the positive and negative electrode plates to obtain a battery cell; the electrolyte of each embodiment and comparative example is poured into the battery cell, and the soft-pack battery is formed to obtain a soft-pack battery, and the working voltage range of the soft-pack battery is 2.5V-4.25V. The batteries containing the electrolyte of each embodiment are recorded as S1-S19, and the batteries containing the electrolyte of each comparative example are recorded as DS1-DS3.

[0131] In addition, a supplementary test example battery S20 is used, and the difference between battery S20 and battery S7 is that the negative electrode active material of battery S20 is replaced by SiOx; a supplementary comparative example battery DS4 is used, and the difference between battery DS4 and battery DS1 is only that the negative electrode active material of battery DS4 is replaced by SiOx.

[0132] (2) Test the battery's room temperature cycle performance test:

[0133] At room temperature (specifically 25℃±1℃), each test battery was charged to 4.25V with a constant current of 0.33C; then discharged to 2.5V with a constant current of 0.33C, at which time the discharge capacity was marked as C0, and the charge and discharge cycle was performed at 1C0 / 1C0 (that is, charging to 4.25V with a constant current of 1C0, and discharging to 2.5V with a constant current of 1C0 was one cycle), and the number of battery charge and discharge cycles when the battery capacity retention rate was 80% was recorded as the battery cycle life. The results are summarized in Table 1.

[0134] (3) Test the high temperature cycle performance of the battery:

[0135] At 25°C, each test battery was charged to 4.25V using a constant current of 0.33C; then discharged to 2.5V at a constant current of 0.33C, at which time the discharge capacity was marked as C0; then at 45°C, a charge and discharge cycle was performed at 1C0 / 1C0 (i.e., charging to 4.25V at a constant current of 1C0, and discharging to 2.5V at a constant current of 1C0 was one cycle), and the number of battery charge and discharge cycles when the battery capacity retention rate was 80% was recorded as the cycle life of the battery at high temperature. The results are summarized in Table 1.

[0136] (4) Test the battery's 50% DCIR (DC internal resistance)

[0137] After adjusting the charge state of each test battery to 50% charge state (SOC), record the battery voltage U1, then discharge at 1.5C for 30s, record the battery discharge terminal voltage U2, and then calculate the 50% DCIR of each battery according to 50% DCIR = (U1-U2) / 1.5C. The results are summarized in Table 1.

[0138] (5) 60℃ storage test

[0139] At 25°C, each test battery was charged to 4.25V with a constant current of 0.33C, and then the constant voltage was 4.25V until 0.05C was cut off, and then the constant current was discharged to 2.5V with a constant current of 0.33C, at which time the discharge capacity was marked as C0; each test battery was fully charged and the volume of the battery was tested; and the battery was stored in an oven at 60°C, and the battery on the 30th day of storage was taken out, cooled to room temperature, and the volume change value of each battery compared with that before storage was tested respectively; and the battery was taken out on the 30th day and cooled to room temperature, and then discharged to 2.5V with a constant current of 0.3C, and the discharge capacity C1 was recorded; it was charged to 4.25V with a constant current of 0.3C, and the constant voltage was 4.25V until 0.05C was cut off, and after being left for 30 minutes, it was discharged to 2.5V with a constant current of 0.3C, and the discharge capacity C2 was recorded;

[0140] High temperature storage residual capacity retention rate (%) = C1 / C0×100%;

[0141] High temperature storage recovery capacity retention rate (%) = C2 / C0×100%. The results are summarized in Table 1.

[0142] (6) Room temperature fast charging capability test

[0143] Take the three-electrode cells of the above test cells respectively and perform the following tests at room temperature:

[0144] ① Connect the blue electric test cabinet according to the conventional test, and use a 3-channel Agilent data acquisition instrument to collect the voltages between the positive and negative electrodes, the positive electrode and the copper wire reference electrode (, and the negative electrode and the copper wire reference electrode; before the test, the copper wire reference electrode is also plated with lithium. Specifically, lithium is plated in the forward direction for 4 hours at a current of 20 μA (connecting the positive electrode and the copper wire reference electrode), and lithium is plated in the reverse direction for 4 hours at a current of 20 μA (connecting the negative electrode and the copper wire reference electrode).

[0145] ② Charge at 0.5C constant current to the upper limit voltage of 4.25V, let it stand for 1h, discharge at 1 / 3C constant current to the lower limit voltage of 2.5V, let it stand for 1h;

[0146] ③ Charge at 1C constant current to the upper limit voltage of 4.25V, let it stand for 1h, discharge at 1 / 3C constant current to the lower limit voltage of 2.5V, let it stand for 1h;

[0147] ④ Charge at 1.5C constant current to the upper limit voltage of 4.25V, let it stand for 1h, discharge at 1 / 3C constant current to the lower limit voltage of 2.5V, let it stand for 1h;

[0148] ⑤ Charge at 2C constant current to the upper limit voltage of 4.25V, let it stand for 1h, discharge at 1 / 3C constant current to the lower limit voltage of 2.5V, let it stand for 1h;

[0149] ⑥ Charge at 3C constant current to the upper limit voltage of 4.25V, let it stand for 1h, discharge at 1 / 3C constant current to the lower limit voltage of 2.5V, let it stand for 1h;

[0150] ⑦ Take the battery SOC state when the negative electrode potential to the reference electrode reaches 0mV at each charging rate, and calculate the charging time required from 10% SOC to 80% SOC; specifically, determine the battery SOC at 0mV at each charging rate through the copper wire reference electrode, first charge to 10% SOC at 0.5C, then charge to 0mV at 3C, the time is recorded as t1, and the corresponding SOC state is a%; then charge to 0mV at 2.5C, and charge to 0mV at 3C. The time is recorded as t2, corresponding to the SOC state of b%; then charged at 2C until the negative electrode potential reaches 0mV, the charging time is recorded as t3, corresponding to the SOC state of c%; then charged at 1.5C until the negative electrode potential reaches 0mV, the charging time is recorded as t4, corresponding to the SOC state of d%; then charged at 1C until the negative electrode potential reaches 0mV, the charging time is recorded as t5, corresponding to the SOC state of 80%, and the charging time from 10% SOC to 80% SOC is t1+t2+t3+t4+t5. The results are summarized in Table 1.

[0151] (7) Fast charging cycle performance test

[0152] At 25°C, each test battery was charged and discharged according to the following cycle strategy: charged at 0.5C for 12 minutes, charged at 3C constant current for 8.9 minutes, charged at 2.5C constant current for 1.2 minutes, then charged at 2C constant current for 1.8 minutes, and then charged at 1.5C constant current for 2.4 minutes; then charged at 1.5C constant current for 5 minutes, then charged at 0.3C constant current to 4.25V and constant voltage to 0.05C, after standing for 30 minutes, discharged at 1C constant current to 2.5V, and this is one cycle. The number of fast charging cycles at which the capacity retention rate decays to 80% is summarized in Table 1.

[0153] Table 1

[0154]

[0155]

[0156] Combining the parameters of each test battery and the data in Table 1, it can be found that in the battery using graphite as the negative electrode active material, compared with the comparative batteries (DS1-DS3), the embodiment batteries S1-S19 can take into account the cycle, high temperature storage and rate performance (specifically reflected in DCIR and fast charging performance).

[0157] By comparing the performance of the batteries S1-S19 of the examples, it can be found that: in S1-S3, when other parameters remain unchanged, adding LiFSI to the electrolyte can improve the battery's cycle, high-temperature storage and fast-charging performance; when a fluoroether solvent is further added, the dissolution of lithium nitrate can be promoted, and the electrolyte can be promoted to infiltrate the battery, so that the battery's cycle and fast-charging performance are better. Comparing the data of batteries S4-S6, it can be found that when the content of LiFSI is within the range further recommended in this application, the overall performance of the battery is better (S6). Among them, high temperature will aggravate the effect of LiFSI on the positive electrode current collector, so the high-temperature storage performance has slightly declined, but the rate performance is better. Comparing the performance of batteries S10-S13, it can be found that when the content of the additive is within the range recommended in this application, it is more conducive to the performance of the battery's rate performance. Comparing the performance of batteries S7 and S14-S17, it can be seen that divinyldiethoxysilane can better take into account the simultaneous improvement of cycle performance and rate performance. Comparing the performance of S7 and S18, it can be seen that the modification effect is better when the ether oxygen atom is directly connected to the Si atom.

[0158] Among batteries using silicon-based negative electrode materials, the battery S20 using the electrolyte provided in the embodiments of the present application is superior to the comparative battery DS4.

[0159] The above is an exemplary embodiment of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made thereto without departing from the principles of the present application. These improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. An electrolyte, characterized in that: Comprising lithium nitrate and an additive as shown in formula (I); Wherein, at least one of R1, R2, R3 and R4 contains an unsaturated bond that can undergo addition polymerization reaction, and at least one of R1, R2, R3 and R4 contains an -OC bond, and the -OC bond is connected to a silicon atom or a carbon atom.

2. The electrolyte according to claim 1, characterized in that The unsaturated bonds include carbon-carbon double bonds and / or carbon-carbon triple bonds.

3. The electrolyte according to claim 1 or 2, characterized in that The R1, R2, R3 and R4 are each independently selected from a substituted or unsubstituted hydrocarbon group containing the unsaturated bond and / or the -OC bond.

4. The electrolyte according to any one of claims 1 to 3, characterized in that One or two of R1, R2, R3 and R4 contain the unsaturated bond.

5. The electrolyte according to any one of claims 1 to 4, characterized in that The -OC bond is connected to the Si atom.

6. The electrolyte according to any one of claims 1 to 5, characterized in that: The number of carbon atoms in R1, R2, R3 and R4 is each independently a positive integer of 1 to 12.

7. The electrolyte according to any one of claims 1 to 6, characterized in that The R1, R2, R3 and R4 are each independently a group other than an H atom and a hydroxyl group.

8. The electrolyte according to claim 3, characterized in that The substituted or unsubstituted hydrocarbon group containing the unsaturated bond includes vinyl and / or ethynyl; the substituted or unsubstituted hydrocarbon group containing the -OC bond includes at least one of methoxy, ethoxy, 2-methoxyethoxy and phenoxy; Preferably, the additive comprises at least one of formula (A) to formula (E), 9. The electrolyte according to any one of claims 1 to 8, characterized in that: Based on the total mass of the electrolyte, the content of the additive is in the range of 0.1% to 5%.

10. The electrolyte according to any one of claims 1 to 9, characterized in that: The mass content of the lithium nitrate in the electrolyte is in the range of 0.1% to 5%.

11. The electrolyte according to any one of claims 1 to 10, characterized in that: The electrolyte also includes lithium bis(fluorosulfonyl)imide; Preferably, the mass content of the lithium bis(fluorosulfonyl)imide in the electrolyte is in the range of 1% to 15.6%.

12. The electrolyte according to any one of claims 1 to 11, characterized in that: The electrolyte also includes a fluoroether solvent as shown in formula (II), Wherein, R5 and R6 are fluoroalkyl groups, wherein the number of carbon atoms of the fluoroalkyl group is a positive integer of 1 to 12.

13. The electrolyte according to claim 12, characterized in that The electrolyte further comprises a carbonate solvent; preferably, the mass ratio of the fluoroether solvent to the carbonate solvent is 1:(1-19).

14. The electrolyte according to any one of claims 1 to 13, characterized in that: The electrolyte also includes an electrolyte salt; the electrolyte salt includes at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium sulfate, lithium difluorooxalatoborate, lithium bistrifluoromethanesulfonamide, lithium hexafluoroarsenate, lithium trifluoromethanesulfonate, lithium dioxalatoborate and lithium perchlorate.

15. A secondary battery, characterized in that: It comprises a negative electrode; the surface of the negative electrode has a solid electrolyte interface film, and the solid electrolyte interface film comprises a silicon-containing flexible polymer and Li3N.

16. The secondary battery according to claim 15, characterized in that: The silicon-containing flexible polymer comprises a polymerization product of at least one additive as represented by formula (I); Wherein, at least one of R1, R2, R3 and R4 contains an unsaturated bond that can undergo addition polymerization reaction, and at least one of R1, R2, R3 and R4 contains an -OC bond, and the -OC bond is connected to a silicon atom or a carbon atom.

17. The secondary battery according to claim 15 or 16, characterized in that: The secondary battery comprises the electrolyte according to any one of claims 1 to 14.

18. The secondary battery according to any one of claims 15 to 17, characterized in that: The negative electrode includes a current collector and a negative electrode active material layer disposed on at least one side of the current collector, wherein the negative electrode active material layer includes a silicon-based negative electrode material.

19. An electrical equipment, characterized in that: The electric device comprises the secondary battery according to any one of claims 15 to 18.

Citation Information

Patent Citations

  • Lithium ion battery electrolyte containing unsaturated bond silane additive and lithium ion battery

    CN113394451A

  • Lithium battery electrolyte and lithium battery

    CN114039090A

  • Nonaqueous electrolyte for secondary battery and nonaqueous electrolyte secondary battery using it

    JP2008277003A